Analisis Kepuasan Pengguna Aplikasi E- Ganesha pada Sistem Absensi Menggunakan Pendekatan PIECES - I Gede Natha Krisna; I Gusti Lanang Agung Raditya Putra; Gede Arna Jude Saskara (POLITEKNIK NEGERI JAKARTA, 2025)
This study analyzes user satisfaction with the attendance system of the e‑Ganesha application using the PIECES framework. The research adopts a quantitative descriptive design, collecting data through a Likert scale questionnaire administered to 170 respondents (85 employees and 85 lecturers) at Undiksha, complemented by open-ended questions to capture richer user feedback. Instrument validity was tested using the Pearson Product Moment correlation (all items met r-hitung > r-tabel), and reliability with Cronbach’s Alpha (α = 0.973), indicating excellent internal consistency. Using the Kaplan and Norton classification, overall satisfaction falls in the “satisfied” category. For employees, the highest mean scores are Information and Control & Security (4.49), while the lowest is Economy (4.29); for lecturers, Information is highest (4.62) and Economy is lowest (4.42). Qualitative responses highlight several areas for improvement: slower system speed during peak hours, error messages that are not sufficiently informative, inefficient leave request and approval flows, and limited administrative controls that may allow misuse. The PIECES analysis identifies strengths in informative outputs and data protection, with weaknesses in performance variability and process efficiency; opportunities include workflow automation and monitoring; threats involve declining user trust if friction persists. Recommendations synthesized via SWOT prioritize performance optimization, usability enhancements, streamlined processes, and governance controls. These findings provide actionable guidance for iterative improvements to e‑Ganesha’s attendance module and contribute to the broader literature on satisfaction evaluation in institutional information systems.